THE ROLE OF AUDIT COMMITTEES IN OMANI BUSINESS CONTEXT: DO THEY AFFECT THE PERFORMANCE OF NON-FINANCIAL COMPANIES - Alabdullah, Tariq Tawfeeq Yousif (Transpublika Publisher, 2023)
In this research, the Muscat Securities Market (MSM) non-financial sector's business profitability is examined in relation to specific audit committee features. Cross-sectional information from 40 non-financial companies' annual reports from 2022 was examined. To test hypotheses and investigate the effects of audit committee characteristics on business profitability, the study used Smart-PLS for data analysis. The findings show that the audit committee's size and independence have a considerable detrimental impact on financial performance. Yet, there is no connection between the quantity of audit committee meetings and the company's success as indicated by the management accounting metric ROA. Mainly, the present research examines the link between the characteristics of independent variables and their impact on the firm financial performance, making it particularly important for Arab Gulf Countries, especially in the period after COVID-19 crisis. The study's contributions have both theoretical and practical implications, offering professionals, legislators, scientists, and scholars working in fields relevant to business performance useful information. To the best of my knowledge, until now, no previous study has done could give evaluation about the impact of audit committee characteristics on the firm financial performance in the Arab Golf Countries, especially in Oman Context after the events of COVID-19. Thus, this research fills the call for the current literature in the field of accounting, management, finance and economy via testing the overall characteristic of the audit committee and their effectiveness on firm financial performance in the context of Arab Golf Countries.